A New Neurocognitive Interpretation of Shoulder Position Sense during Reaching: Unexpected Competence in the Measurement of Extracorporeal Space. (25th December 2016) - Paolucci, Teresa; Zangrando, Federico; Piccinini, Giulia; Sciarra, Federico; Pallotta, Rocco; Mannocci, Alice; la Torre, Giuseppe; Bini, Fabiano; Marinozzi, Franco; Gumina, Stefano; Padua, Luca; Saraceni, Vincenzo Maria
Abstract : Background . The position sense of the shoulder joint is important during reaching. Objective . To examine the existence of additional competence of the shoulder with regard to the ability to measure extracorporeal space, through a novel approach, using the shoulder proprioceptive rehabilitation tool (SPRT), during reaching. Design . Observational case-control study. Methods . We examined 50 subjects: 25 healthy and 25 with impingement syndrome with a mean age [years] of 64.52 +/− 6.98 and 68.36 +/− 6.54, respectively. Two parameters were evaluated using the SPRT: the integration of visual information and the proprioceptive afferents of the shoulder (Test 1) and the discriminative proprioceptive capacity of the shoulder, with the subject blindfolded (Test 2). These tasks assessed the spatial error (in centimeters) by the shoulder joint in reaching movements on the sagittal plane. Results . The shoulder had proprioceptive features that allowed it to memorize a reaching position and reproduce it (error of 1.22 cm to 1.55 cm in healthy subjects). This ability was lower in the impingement group, with a statistically significant difference compared to the healthy group (p < 0 . 05 by Mann–Whitney test). Conclusions . The shoulder has specific expertise in the measurement of the extracorporeal space during reaching movements that gradually decreases in impingement syndrome.